Trends and Disparities in Cardiovascular Death in Sarcoidosis: A Population‐Based Retrospective Study in the United States From 1999 to 2020 - Min Choon Tan; Yong Hao Yeo; Noreen Mirza; Boon Jian San; Jian Liang Tan; Justin Z. Lee; Joanne K. Mazzarelli; Andrea M. Russo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Despite significant cardiac involvement in sarcoidosis, real‐world data on death due to cardiovascular disease among patients with sarcoidosis is not well established. Methods and Results We queried the Centers for Disease Control and Prevention's Wide‐Ranging Online Data for Epidemiologic Research database for data on patients with sarcoidosis aged ≥25 years from 1999 to 2020. Diseases of the circulatory system except ischemic heart disease were listed as the underlying cause of death, and sarcoidosis was stated as a contributing cause of death. We calculated age‐adjusted mortality rate (AAMR) per 1 million individuals and determined the trends over time by estimating the annual percentage change using the Joinpoint Regression Program. Subgroup analyses were performed on the basis of demographic and geographic factors. In the 22‐year study period, 3301 cardiovascular deaths with comorbid sarcoidosis were identified. The AAMR from cardiovascular deaths with comorbid sarcoidosis increased from 0.53 (95% CI, 0.43–0.65) per 1 million individuals in 1999 to 0.87 (95% CI, 0.75–0.98) per 1 million individuals in 2020. Overall, women recorded a higher AAMR compared with men (0.77 [95% CI, 0.74–0.81] versus 0.58 [95% CI, 0.55–0.62]). People with Black ancestry had higher AAMR than people with White ancestry (3.23 [95% CI, 3.07–3.39] versus 0.39 [95% CI, 0.37–0.41]). A higher percentage of death was seen in the age groups of 55 to 64 years in men (23.11%) and women (21.81%), respectively. In terms of US census regions, the South region has the highest AAMR from cardiovascular deaths with comorbid sarcoidosis compared with other regions (0.78 [95% CI, 0.74–0.82]). Conclusions The increase of AAMR from cardiovascular deaths with comorbid sarcoidosis and higher cardiovascular mortality rates among adults aged 55 to 64 years highlight the importance of early screening for cardiovascular diseases among patients with sarcoidosis.